Implementasi Tari Tradisional Kalimantan Timur Dalam Mengembangkan Kecerdasan Kinestetik dan Kognitif Pada Anak Usia Dini di TK Negeri Samarinda - Salamah Salamah; Sy Nurul Shobah; Siti Julaiha (Journal on Education, 2023)
Planning for East Kalimantan traditional dance learning in developing kinesthetic and cognitive intelligence in early childhood, only in Samarinda 1 Public Kindergarten is carried out sequentially as follows; determine learning objectives, select interesting topics, determine projects, determine time frames, determine assessment criteria, provide materials and resources and provide support and guidance. Implementation of East Kalimantan traditional dance learning in developing kinesthetic and cognitive intelligence in early childhood, Samarinda 1 Public Kindergarten, as follows; the teacher selects projects that are relevant and interesting, provides sufficient resources, provides appropriate guidance, encourages collaboration and communication and evaluates learning outcomes. Whereas in TK Negeri 2 Samarinda and TK Negeri 10 Samarinda the teacher only chose which traditional dance themes were appropriate for early childhood and only selected a few children to teach East Kalimantan traditional dance. Evaluation of East Kalimantan traditional dance learning in developing kinesthetic and cognitive intelligence in early childhood, needs to be done to find out to what extent learning objectives have been achieved and how effective East Kalimantan traditional dance learning is in improving children's kinesthetic and cognitive intelligence.